The Influence of Work Experience, Competence, and Task Complexity on the Effectiveness of Accounting Information Systems - Sabilah Amelia; Septi Wulandari Cahirina (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The effectiveness of accounting information systems is an important topic to examine, given the crucial role of these systems in supporting organizational financial decision-making. This study aims to identify factors that influence the effectiveness of accounting information systems, specifically work experience, competence, and task complexity in cooperatives in Tangerang City. This study uses a quantitative approach with a population of accounting information system users in cooperatives in Tangerang City. The sampling technique used purposive sampling, resulting in a sample of 75 respondents. Data analysis was conducted using multiple linear regression analysis with SPSS version 25 software, including validity tests, reliability tests, classical assumption tests, F test, R² test, and t-test. The results show that simultaneously work experience, competence, and task complexity have a significant effect on the effectiveness of accounting information systems with an F value of 7.582 and R² of 0.243. Partially, work experience has a significant positive effect (t=4.145; sig=0.000), while competence (t=-0.367; sig=0.715) and task complexity (t=0.188; sig=0.851) have no significant effect. These findings indicate that improving the effectiveness of accounting information systems is more influenced by user work experience in operating the system. Although competence and task complexity do not show significant effects, this indicates that user-friendly systems and practical user experience are more dominant in determining the successful implementation of accounting information systems in cooperative environments